Structure and detonation performance of a novel HMX/LLM‐105 cocrystal explosive. (12th August 2013) - Lin, He; Zhu, Shun‐Guan; Li, Hong‐Zhen; Peng, Xin‐Hua
Abstract : Intermolecular interactions and properties of octahydro‐1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐ tetrazocine (HMX) / 2, 6‐diamino‐3, 5‐dinitropyrazine‐1‐oxide (LLM‐105) cocrystal were studied by using the dispersion‐corrected density functionals (ωB97XD, B97D) and meta‐hybrid functional (M062x) methods. Binding energies, heats of formation, thermodynamic properties, atoms in molecules, and natural bond orbital analysis were performed to investigate HMX/LLM‐105 complexes. Results show that the mainintermolecular interactions between HMX and LLM‐105 are CH…O, NH…O, N…O, and O…O interactions. In addition, Monte Carlo simulation was employed to predict the crystal structure of HMX/LLM‐105 cocrystal. The HMX/LLM‐105 cocrystal is most likely to crystallize in C 2/c space group, and its corresponding cell parameters are Z = 8, a = 41.63 Å, b = 6.77 Å, c = 45.63 Å, ß = 164.55°, and ρ = 1.99 g/cm 3 . Detonation velocity and pressure of HMX/LLM‐105 cocrystal are 8.95 km/s, 37.69GPa, a little lower than those of HMX (9.10 km/s, 37.76GPa). However, according to the net charges of nitro group, HMX/LLM‐105 cocrystal exhibits less sensitive than HMX. Finally, bond dissociation energy calculation shows that HMX/LLM‐105 complexes are thermally stable. Consideringthermal stability, sensitivity, and detonation performance, HMX/LLM‐105 cocrystal meets the requirements of insensitive high energy density materials. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Previous studies have shown that cocrystal explosive is one of the most promising approaches to decrease sensitivity of high energy materials and maintain their detonation performance. In this work, a novel cocrystal composed of HMX and LLM‐105 was designed and theoretically investigated. Calculation shows that HMX/LM‐105 cocrystal possesses strong intermolecular interactions, insensitivity, thermal stability, and good detonation performance.